The Personality types (The Enneagram) among the lecturers of Baghdad University and its relation to some variables - سيف محمد رديف ميسون كريم ضاري (College of Education for Women, 2019)
The current study is aimed to identify personality types of the lecturers of Baghdad University as well as identify the prevailing types among the lecturers. In addition, the study aimed to identify the significant difference among personality types (The Enneagram) according to the variables of academic title and scientific major . One hundred and ninety four lecturers were involved in this study. In order to achieve the study's aims, the scale of (Baron& Wagele 1994) was used to measure the nine personality types (The Enneagram) that was translated by( Anwar Omar Ibrahim 2012). Some statistical analysis were used and the result demonstrated that Romantic types was found to be the most prevailing types among the lecturers of Baghdad University followed by types of Reformer and Helper. In additions, the result found that there is a significant difference among the types of ( Perfectionism, Achiever, Romantic, Investigator, and Adventure) according to the academic specialization, specifically in human specialization. Regarding to the academic title, the result demonstrated that there is a significant difference in the highest rank of academic titles.